2004
DOI: 10.1161/01.cir.0000124480.32233.8a
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Atherosclerosis as Assessed by Carotid Intima-Media Thickness in Patients With HIV Infection

Abstract: Background-HIV-infected patients may be at increased risk for coronary events. The purpose of this study was to identify predictors of carotid intima-media thickness (IMT) in HIV patients at baseline and to measure IMT progression over 1 year. Methods and Results-We measured blood lipids, inflammatory markers, and IMT in 148 HIV-infected adults (mean age, 45Ϯ8 years) and in 63 age-and sex-matched HIV-uninfected control subjects. The mean duration of HIV infection was 11 years, and the median duration of protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
406
10
17

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 526 publications
(484 citation statements)
references
References 51 publications
48
406
10
17
Order By: Relevance
“…Endothelial dysfunction is also associated with a prothrombotic state,44 and studies which investigated the prothrombotic state in HIV-infected populations showed increased levels of PAI-1 activity and fibrinogen 4,45,46. However, in our study neither the PAI-1 activity nor fibrinogen levels were increased in the HIV-infected subjects, indicating no signs of a prothrombotic state.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Endothelial dysfunction is also associated with a prothrombotic state,44 and studies which investigated the prothrombotic state in HIV-infected populations showed increased levels of PAI-1 activity and fibrinogen 4,45,46. However, in our study neither the PAI-1 activity nor fibrinogen levels were increased in the HIV-infected subjects, indicating no signs of a prothrombotic state.…”
Section: Discussioncontrasting
confidence: 75%
“…Worldwide, various forms of cardiovascular involvement, such as endothelial dysfunction,3 accelerated atherosclerosis4 and coagulation disorders5 have been documented among HIV-infected individuals. In South Africa, atherosclerotic disease, historically not common in most black Africans, is increasing 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several classical CV risk factors including age, gender, body mass index (BMI), blood pressure, increased total cholesterol (TC) levels or tobacco consumption have been previously recognized in HIV+ patients 6 . Surprisingly, there are contradictory reports on the association between low density lipoprotein cholesterol (LDL-C), the most recognized lipid risk factor in non-HIV populations 7 , and CIMT in HIV+ populations [8][9][10][11] . -The fourth sentence was corrected by changing "formed" to "selected" as suggested.…”
mentioning
confidence: 99%
“…We agree that the presence of lipo-accumulation influences the waist perimeter and so we 6 . Surprisingly, there are contradictory reports on the association between low density lipoprotein cholesterol (LDL-C), the most recognized lipid risk factor in non-HIV populations 7 , and CIMT in HIV+ populations [8][9][10][11] . Because classical risk factors do not account for all atherosclerosis risk in HIV+ patients, a search for non-classical could be of interest.…”
mentioning
confidence: 99%